Study on Solar Powered Electric Vehicle with Thermal Management Systems on the Electrical Device Performance - Yusuf Dewantoro Herlambang; Wahyu Sulistiyo; Margana Margana; Nanang Apriandi; Septiantar Tebe Nursaputro; Marliyati Marliyati; Muji Setiyo; Wawan Purwanto; Muhammad Latifur Rochman; Jin Cherng Shyu (Automotive Experiences, 2024)
This study aims to determine the reliability of applying a thermal management system in conjunction with Internet of Things in solar electric cars. In conventional electric cars or those whose driving energy source comes from gasoline fuel; the applied thermal management system is mainly used as a coolant for the internal combustion engine. However, for electric cars the thermal management system may be used for the main components such as controllers that convert solar module energy into electricity and batteries. Results from tests utilizing six DC fans for air cooling of the thermal management system yield two variations of battery charging conditions from the solar modules, namely variations of 25 and 400 turns of the trimmer constant current step-up charger. Test results from the proposed thermal management system show that the highest step-up charger temperature is 35.75 Â°C with voltage of 57.64 V for the variation of 25 laps. The test results on the battery voltage and temperature show that the highest battery temperature reaches 31.75 Â°C with voltage of 57.3 V at the variation of 25 rounds.